PENGARUH KONFLIK PEKERJAAN-KELUARGA TERHADAP KESEJAHTERAAN - Khoirunnisa, Rikha Muftia (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2013)
The most important domain on someoneâs life are work and family. Everyone have specific roles on it, and ideally he/she trying to balance it. But, it will lead work-family conflict as the demand is incompatible each other. Based on role theory, work-family conflict affect someoneâs well-being. Well-being indicate someoneâs happiness and sobriety, so itâs important to concern on it. In the current research, work-family conflict identified into two form, i.e. time-based and strain-based conflict. While well-being measured by job and family satisfaction. Data collected using survey method. The respondents in the current research are headmasters. Data of perceived work-family conflict gained from coupleâs perceive (dyadic). It is aimed to get more valid data about perceived work-family conflict, which rarely done in the prior researches. In the current research, the hypotheses testing used multiple regression analysis. Results showed that only strain-based conflict negatively affect job satisfaction.